Pengaruh Plant Growth Promoting Rhizobakteria (PGPR) terhadap Pertumbuhan dan Hasil Tanaman Kacang Tanah (Arachis hypogaea L.) - I MADE DWI ANJARDITA; I GUSTI NGURAH RAKA; IDA AYU MAYUN; I NYOMAN SUTEDJA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2018)
The Effect of Plant Growth Promoting Rhizobacteria (PGPR) on Growth and Results of Peanut (Arachis hypogaea L.) This study aims to determine the type of rhizobacteria that have better ability to improve the growth and yield of peanut. The design used was randomized block design with 5 treatments is RB35 (undis rooting plants from Beratan, Sukasada), RB36 (undis rooting plants from Kubutambahan, Buleleng), RB3 (kara benguk rooting plants), RB9 (lamtoro rooting plant) and Controls. Each treatment repeated 5 times. This study observed plant height, number of leaves, number of branches, chlorophyll content, number of root nodules, weight of oven dry roots, weight of oven dry stalks, number of pods per plants, number of pods contain per plants, weight of 1000 seeds, dry seeds weight of oven and predicted yield per hectare. The results showed that the four rhizobakteria there are RB35, RB36, RB3 and RB9 able to increase the growth and yield of peanut plants. From the four rhizobacteria, there are 3 rhizobacteria that have higher ability in increasing peanut yield of RB35 (3.72 tons ha-1), RB36 (3.68 tons ha-1) and RB3 (3.50 tons ha-1) compared to RB9 (3.25 tons ha-1) of plants without rhizobacteria or control (2.04 tons ha-1).